Customer brand co-creation: a conceptual model. Issue 6 (7th September 2015) - Ross Brennan; Professor Sue Halliday, Dr; France, Cassandra; Merrilees, Bill; Miller, Dale
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to develop conceptual understanding in the area of customer brand co-creation. The research considers the factors influencing customers to co-create and the impacts of customer co-creation on the brand. Design/methodology/approach – Theoretical development is progressed through conceptualisation of a series of research propositions which consider the antecedents and consequences of brand co-creation. Conceptualisation entails analysing and synthesising previous studies and reasoning new relationships between relevant concepts. Customer brand co-creation theory is improved by operationalizing the concept in a theoretical model. Findings – The Customer Brand Co-creation Model expresses the influence of brand engagement, self-congruity and involvement as antecedents to brand co-creation. Further, the model identifies the moderating effect of brand interactivity and brand communities. Finally, the model actualises the impact of brand co-creation upon brand value and brand knowledge. Research limitations/implications – The conceptual paper explores an emerging area of research interest. The study provides a level of clarity by defining the brand co-creation construct and developing several research propositions and a conceptual model for advancing knowledge of co-creation. Practical implications – The research provides new insight for brand managers who may be investing in co-creation programs and exposing their brand, but without understanding the impact of customer brand co-creation. Conceptual development of theory provides initial insight for practitioners and explores outcomes of co-creation. Originality/value – This work brings together disparate but highly relevant branding theories to progress the co-creation literature and improve understanding of the influence of co-creation upon the brand and customer.